Performance of power allocation under priority user in CR-NOMA - Elmadina, Nahla Nur; Saeid, Elsadig; Mokhtar, Rania A.; Saeed, Rashid A.; Ali, Elmustafa Sayed; Khalifa, Othman Omran (IEEE, 2023)
A promising 5G communications technology was already known as CR-Non-Orthogonal Multiple Access (CRNOMA). Power allocation (PA) and user pairing both affect how well NOMA systems perform. For the PA problem, the majority of recent studies offer suboptimal solutions with high computing complexity that prioritize rate maximization over performance fairness. Furthermore, a thorough search is required for the combined optimization of PA and UP. The primary contribution of this paper is the suggestion of a brand-new, minimally difficult Maximization optimization Data rate based power allocation (MODRFPA) in downlink CR-NOMA. The combined effects of SNR per subcarrier and typically combined channel gains have been thoroughly analyzed and investigated. Users' feedback on NOMA's performance in terms of user fairness and capacity is demonstrated. The outcomes of the simulation demonstrate that the suggested MODRPA can enhance the fairness and data rate of current UP techniques. Additionally, simulation findings demonstrate that the proposed coefficient power performs schemes more effectively and offers performance that is close to ideal